INFLUENCE OF CADMIUM ON GROWTH AND BIOCHEMICAL CONTENTS OF TOMATO PLANTS - P. Vijayarengan, A. Natarajan,; Vijayaragavan, M. (Journal of Plant Stress Physiology)
The increasing concentrations (10, 25, 50, 75 and 100 mg /kg) of soil cadmium on growth and biochemical contents in tomato plants were analysed on 30th sampling days. Control plants were maintained separately. Plants were grown in pots containing 3 kg of air dried sandy loam soil and treated with different concentrations (mg/kg) of cadmium (0, 10, 25, 50, 75 and 100 ). Treatments decreased the growth parameters such as root and shoot length and biochemical constituents such as, protein,(except, proline and phenol content) contents in tomato plants compared to untreated plants. The shoot length of cadmium treated tomato plants was higher than the root length. proline and phenol content of root of tomato plants was higher than the shoot.